Culinary Tourism of Traditional Market Snacks in Jabodetabek - Enggriani, Mimi; Ratu Bilqis, Linda Desafitri; Adawiyah, Robiatul; Maulana, Alifatqul; Rachim, Faiza (Jurnal Penelitian Pariwisata, 2023)
This research aims to find out that market snacks in Jabodetabek are a culinary tourism attraction that attracts visitors to enjoy diverse and delicious food. The research method uses qualitative data analysis starting with data collection involving searching and compiling information obtained through interviews, observation and documentation systematically, with the aim of facilitating understanding and sharing knowledge with others. The research results show that increasing interest in culinary tourism has had a positive impact on traders' businesses, with increased sales and income. Innovation in menus and maintained cleanliness are the keys to maintaining the attractiveness of traditional markets. Market snacks also play a role in preserving culture and have a positive impact on tourism. Government support through regulations and infrastructure is important in the growth of this market. Keywords: Culinary Tourism, Snack Market, Traditional Market